Madame Bovary : costumbres de provincia - Flaubert, Gustave, 1821-1880 (Tiempo de clásicos (Madrid, Spain), 2014)
Emma Bovary, bored by her provincial life, is drawn to a more sophisticated world that will demand a terrible price.